Nurturing productive conflict in South Africa's engineering teams - Farinde, Oluwaseun Moyosore (My University, 2017)
ABSTRACT There are positive aspects to conflict that historically have been overshadowed by the need to quell differences in teams (Ben-Hur, Jonsen, & Kinley, 2010; Farmer & Roth, 1998). Fortunately, the fact that stimulating and nurturing healthy productive conflict can be beneficial to team productivity is coming to light (Jehn, 1994; DeChurch & Marks, 2001; Eisenhardt, Kahwajy, & Bourgeois III, 1997; Vliert & Dreu, 1994; Thomas, 2008; Tjosvold, 2008). Of the five conflict handling styles discussed by Thomas and Kilmann (1977), this study focusses on three that incorporate high levels of cooperation, as this would ideally foster conflict nurturing (collaborate, compromise and concede which is also known as accommodating). Task-based conflict under pressure was researched by means of data gathered from a self-completed online survey. Several internal and external factors can create a variety of pressures that potentially can impact team performance (Tsai & Chi, 2009; Dr. S. Williams, 2016; Shell, 2001). This forms the basis for the first research question: How do engineering team members handle constructive conflict on task-based issues when under pressure? Several literatures propose that conflict handling styles be employed as the situation warrants (Callanan, Benzing, & Perri, 2006; Coburn, 2016; Kilmann & Thomas, 1977). Three pressure scenarios are studied in this research – task outcome, time and relationships. It has also been discussed in literature that if conflict is not handled effectively, from the perspectives of the effector (supervisor) and the receptor (subordinate), further damage may be done to team harmony and performance (Baron, 1988). This forms the basis for the second research question: How effective are the styles chosen to nurture productive conflict by engineering teams from the perspectives of the team subordinates and supervisors? This study finds from the conducted research, that the preferred conflict handling style is  Collaboration when under pressure to realise an outcome  Collaboration when pressured for time  Conceding (accommodating) when under pressure to maintain a relationship. On probing survey data in response to task-based conflict scenarios, the observation is  Most supervisors will compromise under outcome, time or relationship pressure  Most subordinates will collaborate under outcome, time or relationship pressure  Jointly, it is more effective for supervisors and subordinates to collaborate as this style choice garnered the most selection with low variance. Searchable key words: nurturing conflict, conflict management, conflict resolution, engineering team performance, project management, emotional intelligence
M.B.A, Thesis
Keywords: Conflict management, Teams in the workplace -- South Africa.